KAJIAN ELEMEN ESTETIK PADA RUANG TUNGGU GEDUNG DOKTORAL UNIVERSITAS MERCU BUANA JAKARTA - Anggi Dwi Astuti (Narada : Jurnal Desain dan Seni, 2020)
The waiting room is an important part of a building. Because it is a temporary transit space used for waiting activities and is passed route to a building. Meanwhile, the waiting room for the doctoral building at Mercu Buana University not only functions as a space for waiting, but is also used for various activities in the public area such as services related to student affairs, student guidance activities with lecturers, and sometimes a display area for poster exhibitions.  As a space that can be accessed by the public, the design must be able to meet the needs of space and present a beauty that can be enjoyed visually. One of the important parts of interior design that affects visual appearance is the aesthetic element. Aesthetic elements in the form of certain patterns that form composition and are designed using design principles. The research method used is descriptive qualitative to get in-depth results about the aesthetic elements of the Doctoral Building Waiting Room. Qualitative data analysis process by comparing field data with appropriate literature data. This research was studied with the aesthetic theory of D.K. Ching said that the aesthetic of an interior space is formed from the use of design principles, namely proportion, scale, balance, harmony, unity and diversity, rhythm, and emphasis or affirmation. This study aims to determine the aesthetic elements of the Doctoral Building Waiting Room and what design principles are applied. Based on the analysis, the Doctoral Building Waiting Room uses the seven design principles. However, what really looks dominant is the rhythm that comes from the repetition of vertical and horizontal lines on the wall and the balance of the interior building structure, and the placement of furniture.